Potensi Kejadian Burnout pada Mahasiswa Kedokteran di Masa Pandemi Covid-19 - AHMAD FIRDAUS; NURMA YULIYANASARI; GINA NOOR DJALILLAH; MUHAMMAD REZA UTAMA (Universitas Hang Tuah, 2021)
Abstract Covid-19 pandemic has caused universal psychosocial repercussions and mass hysteria among the society and various sectors, including education sector. The online learning or distance learning applied during the pandemic has worsened the stress experienced by medical students. The stress level increased due to gaps in access to learning and excessive assignments given without considering students’ cognitive, affective, and psychomotor domains. Continuous academic stress in the long term would bring negative impacts, leading to lower learning motivation and burnout syndrome. The quality of social relationship has been known to significantly affect anxiety level. Therefore, cooperation from family, community, academic institutions, and government agencies in providing social attention and support is needed. In addition, intrinsic preventions through the improvement of lifestyle, health-related behaviour, religious approaches (The Psychology of Religion), motivation, and self-resilience are also important to avoid burnout syndrome among medical students. This study was conducted to propose insights that are expected helpful in anticipating, preventing and minimizing the occurrence of burnout syndrome which would lead to maladaptive behaviours among medical students